РЕДКОМЕТАЛЛЬНЫЕ МИНЕРАЛЫ МИКРОКЛИНО-КВАРЦЕВЫХ ЖИЛ В ВУЛКАНОГЕННО-ОСАДОЧНЫХ ПОРОДАХ Г. КИТКНЮН (ЛОВОЗЕРСКИЙ МАССИВ) - Иванюк Г.Ю.; Пахомовский Я.А.; Яковенчук В.Н.; Меньшиков Ю.П.; богданова А.Н.; михайлова Ю.А. (My University, 2006)
Described rare-metal mineralization is connected with veins of alkaline granite pegmatites within banded volcanogenic-sedimentary rocks of the Kitknyun Mt,; lens-shaped xenoliths of the rocks occur concordantly among magmatic rocks of layered Lovozero massif. Composition of these veins varies from microcline-quartz up to elpidite-microcline-quartz, and their mineral composition becomes more complicated in the same direction. 14 minerals of Zr, Nb, Ba, Be and REE arc described in details in the paper. Analysis of their mineral associations leads to conclusion that the above mentioned veins represent the separate stage in the whole formation of Lovozero massif- following the trap magmatism and preceding the alkaline stage, and their unusual mineral varieties were provided mainly by the cation-cxchanging processes.
Keywords: 549643